Analysis of Family Financial Management: Maqâshid Sharîa Approach - Ria Nor Syaidatus Sofa; Murniati Mukhlisin (Universitas Darusssalam Gontor, 2020)
This study aims to determine factors that affect family financial management from the maqâshid syarī'ah approach according to Imam al-Ghazali. The predicted factors are family control, family financial education, spiritual quotient, consumption behavior and saving behavior. Data collected using questionnaires distributed through hard copy and online. 110 respondents were collected and analyzed using multiple linear regression. The results indicate that family financial education, consumption behavior and saving behavior have a significant effect on family financial management, while family control and spiritual quotient do not affect family financial management. This research contributes to the development of the maqâshid sharīa perspective in the field of family financial management.